The Effectiveness of Yogyakarta City Regional Regulation Number 1 of 2022 on Waste Management in Tourism Cities - Astuti, Sri Indah; Prasetyoningsih, Nanik (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Sustainable waste management is an important issue in Yogyakarta, where Yogyakarta is a tourist city with the most visitors annually. To overcome the overflowing waste disposal at the Piyungan Integrated Waste Disposal Site (TPST), Bantul, the regional government of the city of Yogyakarta created a new Regional Regulation to update the Yogyakarta City PERDA No. 10 of 2012 became No. 1 of 2022. This PERDA regulates that Yogyakarta waste management can be carried out by the community independently, starting from sorting, re-management, and obtaining incentive funds as support from the local government as a form of motivation. However, in this PERDA, visitor waste management needs to be considered, which cannot be handled again by the community and temporary waste storage depots. Visitors still need to be made aware of independent waste management in Yogyakarta. This ultimately makes people unable to manage their waste independently, which has dangerous effects on health and creates smelly waste in the city of Yogyakarta.